PENINGKATAN KAPASITAS KELOMPOK TANI TARUKO SAIYO DALAM PENGELOLAAN LIMBAH PERTANIAN UNTUK MEWUJUDKAN PERBAIKAN IKLIM MIKRO TANAMAN - Ramadhan, Nugraha; Martinsyah, Rachmad Hersi; Obel, Obel; Ronaldi, Ronaldi; Nugroho, Danang; Al Hakim, Afif; Nadia, Nadia; Rayhaani, Aqila Ahda; Hutauruk, Santa Brightness; Sandi, Nofrita; Reski, Sepri (Jurnal Abdi Insani, 2025)
The Community Partnership Program to Support Business Development is partnering with the Taruko Saiyo Farmers Group in Koto Luar Village, Pauh District, Padang. This farmers' group has approximately 10 hectares of land and has the potential to become a model group in the field of sustainable agriculture. However, several challenges remain, such as limited practices in agricultural waste management, declining soil quality, and farmers' limited literacy and skills in applying appropriate technologies. Based on the identified issues, the solutions offered in this program include: (1) processing agricultural waste into compost, (2) creating biopore infiltration pits, (3) producing biochar from rice husk waste, and (4) implementing agricultural waste mulch made from straw on cultivated crops. This program's primary objective is to enhance partners' capacity in production management and socio-cultural aspects. In addition, this program also aims to improve partners' understanding, skills, and participation in agricultural waste management and the application of appropriate technology to create a more optimal microclimate for plants through the utilization of agricultural waste. Educational and empowerment activities in the Taruko Saiyo Farmer Group have succeeded in increasing the empowerment of farmers, both in terms of production management and socio-cultural aspects. Farmers demonstrated improved understanding and skills in managing agricultural waste by applying appropriate technologies. Additionally, farmer participation in all activities was very high, and some farmers began directly applying the training outcomes on their land. As a sustainability measure, the team also developed technical guidelines and simple documentation that can be used for further learning.